Detention of Child Perpetrators: A Case Study at the Aru Islands Regency Resort Police - Irsan Yusuf; Hadibah Zachra Wadjo; Johan Pieter Elia Rumangun (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
Children aged 14-18 years who are in conflict with the law, the Law on the Juvenile Criminal Justice System (SPPA) mandates that children must be deposited in the Temporary Child Placement Institution (hereinafter abbreviated as LPAS) as a substitute for Rutan which is a temporary place for children during the judicial process Article 1 point 21. The purpose of this research is to examine and analyze the detention carried out by children in looking at the best interests of the child and to examine and analyze the fulfillment of children's rights in the investigation process. This type of research is Empirical Juridical research, which is research with field data as the main source of data such as interview results and observations. The results of the research found are that the placement of children in a special room for children is also inadequate, the investigation process in the juvenile criminal justice system should prioritize the best interests of the child and strive for a family atmosphere where the investigator is obliged to ask for consideration or advice from community supervisors. Investigation, arrest and detention will have an impact on the imposition of criminal sanctions of imprisonment as long as the principle of